A Modified in vitro Clot Lysis Assay Predicts Outcomes in Non-traumatic Intracerebral Hemorrhage Stroke Patients—The IRONHEART Study - Orbán-Kálmándi, Rita; Árokszállási, Tamás; Fekete, István; Fekete, Klára; Héja, Máté; Tóth, Judit; Sarkady, Ferenc; Csiba, László; Bagoly, Zsuzsa (Frontiers in Neurology, 2021)
Background: Non-traumatic intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes and results in a higher rate of mortality as compared to ischemic strokes. In the IRONHEART study, we aimed to find out whether a modified in vitro clot lysis assay method, that includes the effect of neutrophil extracellular traps (NETs) might predict ICH outcomes. Patients and Methods: In this prospective, observational study, 89 consecutive non-traumatic ICH patients were enrolled. Exclusion criteria included aneurysm rupture, cancer, liver- or kidney failure or hemorrhagic diathesis. On admission, detailed clinical and laboratory investigations were performed. ICH volume was estimated based on CT performed on admission, day 14 and 90. A conventional in vitro clot lysis assay (CLA) and a modified CLA (mCLA) including cell-free-DNA and histones were performed from stored platelet-free plasma taken on admission. Clot formation and lysis in case of both assays were defined using the following variables calculated from the turbidimetric curves: maximum absorbance, time to maximum absorbance, clot lysis times (CLT) and area under the curve (CLA AUC). Long-term ICH outcomes were defined 90 days post-event by the modified Rankin Scale (mRS). All patients or relatives provided written informed consent. Results: Patients with more severe stroke (NIHSS>10) presented significantly shorter clot lysis times of the mCLA in the presence of DNA and histone as compared to patients with milder stroke [10%CLT: NIHSS 0–10: median 31.5 (IQR: 21.0–40.0) min vs. NIHSS>10: 24 (18–31.0) min, p = 0.032]. Shorter clot lysis times of the mCLA showed significant association with non-survival by day 14 and with unfavorable long-term outcomes [mRS 0–1: 36.0 (22.5.0–51.0) min; mRS 2–5: 23.5 (18.0–36.0) min and mRS 6: 22.5 (18.0–30.5) min, p = 0.027]. Estimated ICH volume showed significant negative correlation with mCLA parameters, including 10%CLT (r = −0.3050, p = 0.009). ROC analysis proved good diagnostic performance of mCLA for predicting poor long-term outcomes [AUC: 0.73 (0.57–0.89)]. In a Kaplan-Meier survival analysis, those patients who presented with an mCLA 10%CLT result of >38.5 min on admission showed significantly better survival as compared to those with shorter clot lysis results (p=0.010). Conclusion: Parameters of mCLA correlate with ICH bleeding volume and might be useful to predict ICH outcomes.